Association of early surgery and absence of ataxia with full recovery after spinal intramedullary ependymoma resection - Alhalabi, Obada; Heene, Stefan; Landré, Vincent; Neumann, Jan-Oliver; Haux-Nettesheim, Daniel; Zweckberger, Klaus; Unterberg, Andreas; Younsi, Alexander (Journal of neurosurgery. Spine, 2024)
OBJECTIVE Spinal intramedullary ependymomas (IEs) represent a well-defined tumor entity usually warranting resection. Factors that determine full long-term neurological recovery after resection are seldomly reported on in larger clinical series. In this study, the authors aimed to highlight the neurological outcome of patients with IEs after resection, with a focus on full neurological recovery, and to explore possible risk factors for the absence of neurological amelioration to an optimal function after surgical treatment. METHODS A single-center retrospective analysis of all patients undergoing surgery for IEs between 2007 and 2021 was performed. Data collection included patient demographics, symptoms, clinical findings, histopathological diagnosis, surgical procedures, complications, and neurological outcome. Patients harboring a favorable outcome (modified McCormick Scale [mMS] grade of I) were compared with patients with a less favorable outcome (mMS grade ≥ II) at the final follow-up. RESULTS In total, 72 patients with a histologically diagnosed IE were included. IEs in those patients (41 males, 31 females; median age 51 [IQR 40-59] years) mostly occurred in the cervical (n = 40, 56%) or thoracic (n = 23, 32%) spine. Upon admission, motor deficits or gait deficits (mMS grade ≥ II) were present in 29 patients (40%), with a median mMS grade of II (IQR I-II). Gross-total resection was achieved in 60 patients (90%), and the rate of surgical complications was 7%. Histopathologically, 67 tumors (93%) were classified as WHO grade 2 ependymomas, 3 (4%) as WHO grade 1 subependymomas, and 2 (3%) as WHO grade 3 anaplastic ependymomas. After a mean follow-up of 863 ± 479 days, 37 patients (51%) had a fully preserved neurological function and 62 patients (86%) demonstrated an mMS grade of I or II. Comparison of favorable with unfavorable outcomes revealed an association of early surgery (within a year after symptom onset), the absence of ataxia or gait disorders, and a low mMS grade with full neurological recovery at the final follow-up. A subgroup of patients (n = 15, 21%) had nonresolving deterioration at the final follow-up, with no significant differences in relevant variables compared with the rest of the cohort. CONCLUSIONS The data presented solidify the role of early surgery in the management of spinal IEs, especially in patients with mild neurological deficits. Furthermore, the presence of gait disturbance or ataxia confers a higher risk of incomplete long-term recovery after spinal ependymoma resection. Because a distinct subgroup of patients had nonresolving deterioration, even when presenting with an uneventful history, further analyses into this subgroup of patients are required.
Veröffentlicht: 03. November 2023
Gesehen am 24.05.2024